Pengaruh Celebrity Endorser, Digital Marketing Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Produk Kosmetik Emina - Claudia Putri, Repi; Sri Handayani, Langgeng (GEMA EKONOMI, 2023)
The rapid development of information technology causes consumers to easily find out information about the whereabouts of a product. This condition requires companies to respond to consumer desires and provide clear information about their products in order to get a positive response from consumers. This study aims to determine the influence of celebrity endorsers, digital marketing and consumer trust on purchasing decisions either partially. This type of research uses quantitative research. The results of the study show that there is a positive and significant influence between Celebrity Endorsers on Purchasing Decisions. This shows that the increasing celebrity endorser variable, the influence on purchasing decisions is getting higher. The results of the study show that there is a positive and significant influence between Digital Marketing on Purchasing Decisions. This shows that the increasing digital marketing variable, the higher the influence on purchasing decisions. The results of the study show that there is no positive and insignificant influence between Consumer Confidence on Purchasing Decisions. This shows that the decreasing consumer trust variable, the influence on purchasing decisions decreases